Development of models of alternative methods of airplanes noise certification - Запорожець, О. І. (Proceedings of National Aviation University (archive), 1998)
Proved is the possibility of using the developed acoustic models of the airplanes for development and substantiation of equivalent methods of their noise certification pursuant to the ICAO requirements. The outcomes of the proof are adduced by matching the computational data with outcomes of certified tests of airplane 11-86. The method has shown sufficient efficiency both for modification of an airplane and for modification of the engine